Permasalahan Status Hukum Dan Kewarganegaraan Anak Hasil Surrogacy Di Luar Negeri: Tinjauan Hukum Perdata Internasional - Ria Indah Sari; Ade Rahma Dini Chairunisah; Dian Adalia (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Transnational surrogacy involving Indonesian citizens creates complex conflicts in Private International Law (PIL) due to contradictions between the legality of the practice in the country of birth and the implicit prohibition under Indonesian law (Health Act No. 36 of 2009, Article 127 paragraph (2)). This study examines the mechanism of choice of law in PIL, as well as the determination of legal parentage and citizenship status of children born through foreign surrogacy. The analysis reveals that although PIL applies connecting factors such as lex loci celebrationis and lex patriae, the recognition of a child’s legal status in Indonesia is strictly limited by the doctrine of Public Order (Ordre Public). Surrogacy contracts are considered null and void as they violate morality and national ethics. Based on the principle that the legal mother is the woman who gives birth, Indonesian courts recognize the surrogate as the lawful mother, severing civil ties with the intended parents. Although the child may still obtain Indonesian citizenship as a form of human rights protection, this is classified as a child born out of wedlock (Article 4(g/h) of the Citizenship Law). Such classification is deemed discriminatory and contrary to the Best Interests of the Child, highlighting the urgent need for a Parentage Order mechanism to ensure legal certainty and protect fundamental child rights.